Positive electrode active material for secondary battery, and positive electrode and lithium secondary battery comprising same
A nickel-rich NCM-based lithium composite transition metal oxide with controlled over-firing and specific crystal structure enhances thermal stability, addressing issues of resistance and side reactions, thereby improving charge/discharge efficiency and output characteristics.
Patent Information
- Application Number
- CN202411499207.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-29
- Filing Date
- 2021-01-19
- Publication Date
- 2024-12-31
AI Technical Summary
Existing nickel-rich NCM-based lithium composite transition metal oxides face issues with thermal stability, increased resistance, and side reactions due to uncontrolled over-firing, leading to degraded charge/discharge efficiency and reduced output characteristics.
A nickel-rich NCM-based lithium composite transition metal oxide is formed as a single particle with a specific crystal structure ratio of Fd3M to Fm3m in a 100 nm region, enhancing thermal stability and surface characteristics through controlled over-firing.
Improves charge/discharge efficiency, output characteristics, and high-temperature life characteristics by suppressing side reactions and resistance, while maintaining high capacity.
Smart Images

Figure CN119230818A_ABST
Abstract
Description
[0001] This application is a divisional application. The international application number of the original application is PCT / KR2021 / 000733, the application number of the Chinese national phase is 202180009819.2, the application date is January 19, 2021, and the name of the invention is "Positive electrode active material for secondary battery and lithium secondary battery containing the same".
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims priority to and the benefit of Korean Patent Application No. 10-2020-0010693, filed on January 29, 2020, the disclosure of which is incorporated herein by reference. Technical Field
[0004] The present invention relates to a positive electrode active material for a secondary battery and a lithium secondary battery comprising the same. Background Art
[0005] Recently, with the rapid popularization of electronic devices using batteries such as mobile phones, laptops, electric vehicles, etc., the demand for secondary batteries with small size, light weight and relatively high capacity is rapidly increasing. In particular, lithium secondary batteries have attracted attention as driving power sources for portable devices due to their light weight and high energy density. Therefore, research and development efforts for improving the performance of lithium secondary batteries are continuously being carried out.
[0006] Lithium secondary batteries generate electrical energy through oxidation and reduction reactions when lithium ions are inserted into / deintercalated from the positive and negative electrodes, wherein an organic electrolyte solution or a polymer electrolyte solution fills the empty space between the positive and negative electrodes, wherein the positive and negative electrodes are composed of active materials capable of inserting and deintercalating lithium ions.
[0007] As positive electrode active materials for lithium secondary batteries, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2, LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4), etc. have been used. Among them, lithium cobalt oxide (LiCoO2) is widely used due to its high operating voltage and excellent capacity characteristics, and is applied as a positive electrode active material for high voltage operation. However, due to the rising price of cobalt (Co) and its unstable supply, the large-scale use of lithium cobalt oxide as a power source in the field of electric vehicles, etc. is limited, and therefore the need to develop positive electrode active materials that can replace lithium cobalt oxide has been proposed.
[0008] Therefore, a nickel-cobalt-manganese-based lithium composite transition metal oxide (hereinafter referred to as "NCM-based lithium composite transition metal oxide") has been developed, in which part of cobalt (Co) is replaced by nickel (Ni) and manganese (Mn). Recently, research has been conducted to increase the capacity by increasing the Ni content in the NCM-based lithium composite transition metal oxide. However, in the case of a Ni-rich positive active material with a high nickel content, as the nickel content increases, thermal stability decreases, resistance increases due to more and more side reactions occurring during the electrochemical reaction, and more and more gas is generated.
[0009] In order to compensate for the above problems, attempts have been made to reduce the interface of the secondary particles to the greatest extent by over-firing by increasing the firing temperature when preparing the positive electrode active material, thereby improving problems such as reduced thermal stability and side reactions and increased resistance. However, since it is difficult to control the over-firing while increasing the firing temperature and the degree of over-firing cannot be properly adjusted, there is a problem of performance degradation, such as reduced charge / discharge efficiency, increased resistance, etc.
[0010] [Related Literature]
[0011] [Patent Document]
[0012] (Patent Document 1) Korean Patent Publication No. 2019-0068484 Summary of the invention
[0013] [Technical issues]
[0014] The present invention aims to provide a positive electrode active material, which is a nickel (Ni)-rich NCM-based lithium composite transition metal oxide and is formed in the form of a single particle by over-firing, so that the thermal stability is improved, the increase of side reactions and resistance is suppressed, and the surface characteristics of the particles when the single particle is formed are improved, thereby improving the charge / discharge efficiency, output characteristics and high temperature life characteristics.
[0015] [Technical solution]
[0016] One aspect of the present invention provides a positive electrode active material for a secondary battery, which is a lithium composite transition metal oxide and has an average particle size (D 50), the lithium composite transition metal oxide containing nickel, cobalt and manganese, the nickel content of which accounts for more than 60 mol% of metals other than lithium, wherein a 100 nm region extending from the particle surface to the center of the lithium composite transition metal oxide has a crystal structure of a Fd3M space group and a Fm3m space group, and a phase ratio (Fd3M / Fm3m) measured in a cross-sectional image of the particle surface portion of the lithium composite transition metal oxide particle obtained using transmission electron microscopy (TEM) is 0.2 to 0.7, and the phase ratio is the ratio of the maximum straight line length of the portion occupied by the crystal structure of the Fd3M space group to the crystal structure of the Fm3m space group.
[0017] Another aspect of the present invention provides a positive electrode and a lithium secondary battery including the positive electrode active material.
[0018] [Beneficial Effects]
[0019] According to the present invention, the positive electrode active material of the NCM-based lithium composite transition metal oxide rich in nickel (Ni) is formed in the form of a single particle, so that the thermal stability is improved, the increase of side reactions and resistance is suppressed, and the surface characteristics are improved by controlling the crystal structure of the particle surface when the single particle is formed, thereby improving the charge / discharge efficiency, output characteristics and high temperature life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a transmission electron microscope (TEM) image of a cross section of the positive electrode active material prepared in Example 2. DETAILED DESCRIPTION
[0021] Hereinafter, the present invention will be described in more detail to facilitate understanding of the present invention. Based on the concept that the inventor can appropriately define terms in order to explain the present invention in the best way, the terms and words used in this specification and claims should not be interpreted as limited to the common meaning or the meaning in the dictionary, but should be interpreted as the meaning and concept consistent with the technical scope of the present invention.
[0022] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. The average particle size (D 50 ) can be measured by, for example, laser diffraction. For example, the average particle size (D 50 ) can be measured by dispersing the positive electrode active material particles in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size analyzer (e.g., Microtrac MT 3000), irradiating with ultrasonic waves at a frequency of about 28 kHz and an output of 40 W, and then calculating the average particle size (D) corresponding to 50% of the cumulative volume in the analyzer. 50 ).
[0023] In this specification, "positive electrode active material in the form of a single particle" is a concept relative to a positive electrode active material in the form of spherical secondary particles formed by agglomerating tens to hundreds of primary particles using a conventional method, and means a positive electrode active material formed of at most 10 primary particles. Specifically, the positive electrode active material in the form of a single particle used herein may be in the form of a single particle formed of one primary particle, or in the form of a secondary particle formed by agglomerating several primary particles.
[0024] In this specification, “primary particle” means the smallest particle unit recognized when a positive electrode active material is observed by a scanning electron microscope, and “secondary particle” means a secondary structure formed by agglomerating a plurality of primary particles.
[0025] In this specification, over-firing means firing at a temperature 50°C to 200°C higher than the approximately suitable firing temperature when preparing a positive electrode active material. For example, when preparing a lithium composite transition metal oxide having a molar ratio of Ni:Co:Mn of 85:5:10 as a positive electrode active material, 690°C to 790°C is known to be a generally suitable firing temperature, but over-firing means firing at 800°C to 900°C.
[0026] <Positive Electrode Active Material>
[0027] The positive electrode active material for a secondary battery of the present invention is a lithium composite transition metal oxide and has an average particle size (D 50 ), the lithium composite transition metal oxide containing nickel, cobalt and manganese, the nickel content of which accounts for more than 60 mol% of metals other than lithium, wherein a 100 nm region extending from the particle surface to the center of the lithium composite transition metal oxide has a crystal structure of a Fd3M space group and a Fm3m space group, and a phase ratio (Fd3M / Fm3m) measured in a cross-sectional image of the particle surface portion of the lithium composite transition metal oxide particle obtained using transmission electron microscopy (TEM) is 0.2 to 0.7, and the phase ratio is the ratio of the maximum straight line length of the portion occupied by the crystal structure of the Fd3M space group to the crystal structure of the Fm3m space group.
[0028] The positive electrode active material of the present invention is an NCM-based lithium composite transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn). The lithium composite transition metal oxide is an NCM-based lithium composite transition metal oxide rich in nickel (Ni), and its nickel content accounts for more than 60 mol% of the total metal content excluding lithium (Li). More preferably, the nickel (Ni) content can account for more than 70 mol%, and even more preferably 80 mol% or more. When the nickel (Ni) content in the lithium composite transition metal oxide accounts for more than 60 mol% of the total metal content excluding lithium (Li), a higher capacity can be ensured.
[0029] The lithium composite transition metal oxide can be represented by the following Chemical Formula 1.
[0030] [Chemical Formula 1]
[0031] Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ
[0032] In Chemical Formula 1, Q is one or more elements selected from the group consisting of Al, Mg, V, Ti, and Zr, and satisfies 1.0 ≤ a ≤ 1.2, 0 < b ≤ 0.4, 0 < c ≤ 0.3, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.4, and -0.1 ≤ δ ≤ 1.0.
[0033] In the lithium composite transition metal oxide represented by Chemical Formula 1, the content of Li can correspond to a, that is, satisfies 1.0 ≤ a ≤ 1.2. When a is less than 1.0, there is a risk that the capacity may decrease. When a exceeds 1.2, the particles sinter during the firing process, so it may be difficult to prepare the positive electrode active material. Considering the balance between the significance of the effect of improving the capacity characteristics of the positive electrode active material according to the Li content control and the sinterability during the preparation of the active material, the more preferable content of Li can satisfy 1.1 ≤ a ≤ 1.2.
[0034] In the lithium composite transition metal oxide represented by Chemical Formula 1, the content of Ni can correspond to 1 - (b + c + d), for example, satisfies 0.6 ≤ 1 - (b + c + d) < 1. When the Ni content in the lithium composite transition metal oxide represented by Chemical Formula 1 is 0.6 or more, a sufficient amount of Ni contributing to charge and discharge is ensured, so the increase in capacity can be promoted. More preferably, the content of Ni can satisfy 0.80 ≤ 1 - (b + c + d) ≤ 0.99.
[0035] In the lithium composite transition metal oxide represented by Chemical Formula 1, the content of Co can correspond to b, for example, satisfying 0 < b ≤ 0.4. When the Co content in the lithium composite transition metal oxide represented by Chemical Formula 1 exceeds 0.4, there is a risk that the cost may increase. Considering that including Co has the effect of significantly improving the capacity characteristics, Co can be contained. More specifically, the content of Co satisfies 0.05 ≤ b ≤ 0.2.
[0036] In the lithium composite transition metal oxide represented by Chemical Formula 1, the content of Mn can correspond to c, for example, satisfying 0 < c ≤ 0.3. When c in the lithium composite transition metal oxide represented by Chemical Formula 1 exceeds 0.3, there is a risk that the output characteristics and capacity characteristics of the battery may decrease. Mn can be contained. More specifically, the content of Mn satisfies 0.05 ≤ c ≤ 0.2.
[0037] In the lithium composite transition metal oxide represented by Chemical Formula 1, Q can be a doping element contained in the crystal structure of the lithium composite transition metal oxide, and the content can correspond to d, that is, satisfying 0 ≤ d ≤ 0.1.
[0038] The positive electrode active material of the lithium composite transition metal oxide of the present invention is in the form of single particles having an average particle diameter (D 50 ) of 1 to 10 μm. More preferably, the average particle diameter (D 50 ) can be 2 to 7 μm, and even more preferably 3 to 6 μm. When the positive electrode active material of the lithium composite transition metal oxide is in the form of single particles formed by primary particles, the thermal stability can be enhanced, and the generation of side reactions can be improved.
[0039] The method for forming single particles is not particularly limited. Generally, single particles can be formed by over-firing while increasing the firing temperature. In addition, additives that contribute to over-firing can be used or the starting materials can be changed to prepare single particles. When single particles are formed as described above, the thermal stability can be enhanced, and the increase in side reactions and resistance can be suppressed. The positive electrode active material in the form of single particles can be formed, for example, by adding a lithium source (such as LiOH, Li2CO3, etc.) to a composite transition metal hydroxide containing nickel, cobalt, and manganese (such as Ni 0.85 Co 0.05 Mn 0.10 (OH)2), then mixing them, and performing over-firing at 800 °C to 900 °C for 10 hours to 25 hours in an oxygen atmosphere.
[0040] According to the positive electrode active material of the present invention, a 100nm region extending from the particle surface to the center of the lithium composite transition metal oxide has a crystal structure of the Fd3M space group and the Fm3m space group, and the phase ratio (Fd3M / Fm3m) measured in a cross-sectional image of the particle surface portion of the lithium composite transition metal oxide particle obtained using transmission electron microscopy (TEM) is 0.2 to 0.7, and the phase ratio is the ratio of the maximum straight line length of the portion occupied by the crystal structure of the Fd3M space group and the crystal structure of the Fm3m space group.
[0041] In the present invention, the crystal structure and phase ratio of the surface of the positive electrode active material can be obtained by using TEM to obtain a cross-sectional image of the surface portion of the particle, then analyzing the phase and calculating the ratio of the maximum straight line length of the portion occupied by the crystal structure of the Fd3M space group and the crystal structure of the Fm3m space group (Fd3M / Fm3m).
[0042] According to the positive electrode active material of the present invention, since the 100nm region extending from the surface to the center of a single particle has a mixture of crystal structures of the Fd3M space group and the Fm3m space group, and the relative ratio (Fd3M / Fm3m) satisfies the range of 0.2 to 0.7, the surface characteristics of the single particle can be improved, and the charge / discharge efficiency, output characteristics and high temperature life characteristics can be enhanced.
[0043] Specifically, when the phase ratio (Fd3M / Fm3m) in a 100nm region extending from the surface to the center of a single particle is less than 0.2, the rate characteristics and output characteristics (room temperature and low temperature output) may be reduced, and when the phase ratio exceeds 0.7, the surface reactivity and life characteristics (capacity retention rate and resistance growth rate) may be reduced.
[0044] More preferably, the phase ratio (Fd3M / Fm3m) in a 100 nm region extending from the surface toward the center of the single particle may be 0.3 to 0.6, and even more preferably 0.35 to 0.5.
[0045] In addition, more preferably, a 500 nm region extending from the particle surface of the lithium composite transition metal oxide toward the center may have a crystal structure of the Fd3M space group and the Fm3m space group, and the phase ratio (Fd3M / Fm3m) may be 0.2 to 0.7, more preferably 0.35 to 0.5.
[0046] The positive electrode active material of an embodiment of the present invention can be formed by mixing the positive electrode active material with a lithium source and adjusting the preparation process conditions, such as adding a firing additive during firing, adjusting the firing temperature, adjusting the molar ratio (Li / M) of lithium to metal (M) other than lithium, adjusting the size and form of the raw materials, etc., but the present invention is not particularly limited to the above-mentioned preparation process conditions.
[0047] The molar ratio (Li / M) of lithium to metal (M) other than lithium in the lithium composite transition metal oxide positive electrode active material may be 1.1 to 1.2, preferably 1.11 to 1.18, more preferably 1.12 to 1.16. When the molar ratio (Li / M) of lithium to metal (M) other than lithium satisfies the range of 1.1 to 1.2, it can contribute to the improvement of crystallinity and can produce a fluxing effect during firing.
[0048] The cation mixing ratio of nickel cations in the lithium layer in the structure of the lithium composite transition metal oxide positive electrode active material of the present invention can be 1.5% or less, preferably 1.0% or less, and more preferably 0.8% or less. When the cation mixing ratio of nickel cations in the lithium layer satisfies the range of 1.5% or less, the irreversible sites in the bulk part of the positive electrode active material can be reduced, thereby promoting the diffusion of lithium ions, and improving the increase in resistance, so that the charging / discharging efficiency, etc. are improved.
[0049] <Positive Electrode and Lithium Secondary Battery>
[0050] Another aspect of the present invention provides a positive electrode for a secondary battery and a lithium secondary battery comprising the positive electrode active material.
[0051] Specifically, the positive electrode includes a positive electrode collector and a positive electrode active material layer, and the positive electrode active material layer is formed on the positive electrode collector and contains the positive electrode active material.
[0052] In the positive electrode, the positive electrode collector is not particularly limited as long as it does not cause chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc., can be used as the positive electrode collector. In addition, the thickness of the positive electrode collector is generally 3μm to 500μm, and may have fine irregularities formed on its surface to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used arbitrarily in various forms, such as films, sheets, foils, nets, porous materials, foams, and non-woven fabrics.
[0053] The positive electrode active material layer may further include a conductive material and a binder in addition to the above-mentioned positive electrode active material.
[0054] The conductive material is used to impart conductivity to the electrode, and any conductive material that does not cause chemical changes in the battery and has electronic conductivity can be used without particular limitation. Specific examples of conductive materials include: graphite, such as natural graphite or artificial graphite, etc.; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber, etc.; metal powder or metal fiber containing copper, nickel, aluminum or silver, etc.; conductive whiskers, such as zinc oxide or potassium titanate, etc.; conductive metal oxides, such as titanium oxide, etc.; and conductive polymers, such as polyphenylene derivatives, etc., which can be used alone or in combination of two or more thereof. The content of the conductive material can generally be 1 to 30% by weight relative to the total weight of the positive electrode active material layer.
[0055] Binders are used to improve the adhesion between the positive active material particles and the adhesion between the positive active material and the positive current collector. Specific examples of binders include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber and various copolymers thereof, which can be used alone or in combination of two or more thereof. Relative to the total weight of the positive active material layer, the content of the binder can be 1 to 30 weight %.
[0056] In addition to using the above-mentioned positive electrode active material, the positive electrode can be manufactured by a conventional positive electrode manufacturing method. Specifically, a positive electrode active material layer-forming composition comprising the above-mentioned positive electrode active material and an optional binder and a conductive material can be applied to the positive electrode current collector, and then dried and rolled to manufacture the positive electrode. In this case, the types and contents of the positive electrode active material, binder and conductive material have been described above.
[0057] As the solvent, a commonly used solvent in the art can be used, and examples of the solvent include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, and water, etc., which can be used alone or in combination of two or more thereof. Considering the thickness of the applied slurry and the manufacturing yield, the amount of the solvent is just enough to dissolve or disperse the positive electrode active material, the conductive material, and the binder, and has a viscosity that can achieve excellent thickness uniformity when applied for the subsequent manufacture of the positive electrode.
[0058] According to another method, the positive electrode may be manufactured by laminating a film, which is obtained by casting a composition for forming a positive electrode active material layer on a separate support and removing it from the support, on a positive electrode current collector.
[0059] Another aspect of the present invention provides an electrochemical device comprising the positive electrode, which may be a battery or a capacitor, and more specifically a lithium secondary battery.
[0060] The lithium secondary battery specifically includes a positive electrode, a negative electrode disposed facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. The positive electrode has been described above. In addition, the lithium secondary battery may also optionally include: a battery container for accommodating an electrode assembly including a positive electrode, a negative electrode, and a separator; and a sealing member for sealing the battery container.
[0061] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.
[0062] The negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the battery and has high conductivity. For example, as the negative electrode current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel or aluminum-cadmium alloy whose surface is treated with carbon, nickel, titanium, silver, etc., can be used. In addition, like the positive electrode current collector, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and has fine irregularities formed on its surface to improve the adhesion of the negative electrode active material. In addition, the negative electrode current collector can be used arbitrarily in various forms, such as films, sheets, foils, nets, porous materials, foams, and non-woven fabrics.
[0063] The negative electrode active material layer comprises a negative electrode active material, and optionally a binder and a conductive material. For example, the negative electrode active material layer can be formed by applying a negative electrode forming composition comprising a negative electrode active material, and optionally a binder and a conductive material to a negative electrode current collector and then drying it; or, laminating a film on the negative electrode current collector, the film being obtained by casting the negative electrode forming composition on a separate support and removing it from the support.
[0064] As the negative electrode active material, a compound that can reversibly intercalate and deintercalate lithium can be used. Specific examples of the negative electrode active material include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber or amorphous carbon; metal materials that can alloy with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy; metal oxides that can be doped and dedoped with lithium, such as SiO β(0<β<2), SnO2, vanadium oxide or lithium vanadium oxide; or a composite comprising the above metal materials and carbonaceous materials, such as a Si-C composite or a Sn-C composite, which can be used alone or in combination of two or more thereof. In addition, a lithium metal film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon, etc. can be used as carbon materials. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch, etc.
[0065] Otherwise, the binder and the conductive material may be the same as those described above for the positive electrode.
[0066] Meanwhile, in lithium secondary batteries, the separator is used to separate the negative electrode and the positive electrode and provide a path for the migration of lithium ions. As a separator, any separator commonly used in lithium secondary batteries can be used without particular limitation, in particular, it is preferred that the migration of electrolyte ions exhibits low resistance and has excellent electrolyte impregnation ability. Specifically, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer or ethylene / methacrylate copolymer, etc.) can be used, or a laminated structure having more than two layers thereof. In addition, a general porous non-woven fabric can be used, for example, a non-woven fabric made of high melting point glass fiber or polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a coated separator can be used, which includes a ceramic component or a polymer material, and is optionally in the form of a single layer or multilayer structure.
[0067] In addition, as the electrolyte used in the present invention, an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, an inorganic solid electrolyte or a molten inorganic electrolyte that can be used to prepare a lithium secondary battery can be used, but the present invention is not limited thereto.
[0068] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0069] As the organic solvent, any solvent that can serve as a medium through which ions involved in the electrochemical reaction of the battery can migrate can be used without particular limitation. Specifically, the organic solvent can be: an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran, etc.; a ketone solvent such as cyclohexanone, etc.; an aromatic hydrocarbon solvent such as benzene or fluorobenzene, etc.; a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC), etc.; an alcohol solvent such as ethanol or isopropanol, etc.; a nitrile such as R-CN (R is a C2-C having a linear, branched or cyclic structure); 20 Hydrocarbons, and may include double bond aromatic rings or ether bonds) and the like; amides, such as dimethylformamide and the like; dioxolanes, such as 1,3-dioxolanes and the like; or cyclopentane. Among those listed above, carbonate solvents are preferred, and more preferably a mixture of a cyclic carbonate compound having high ionic conductivity and a high dielectric constant (such as EC, PC, etc.) and a chain carbonate compound having a low viscosity (such as EMC, DMC, DEC, etc.), which can improve the charge / discharge performance of the battery. In this case, when a mixture obtained by mixing a cyclic carbonate compound and a chain carbonate compound in a volume ratio of about 1:1 to about 1:9 is used, excellent electrolyte performance can be exhibited.
[0070] As a lithium salt, any compound capable of providing lithium ions for a lithium secondary battery can be used without particular limitation. Specifically, as a lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. can be used. The lithium salt is preferably used in a concentration of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has an appropriate level of conductivity and viscosity, and therefore can exhibit excellent electrolyte performance, and lithium ions can be effectively migrated.
[0071] In addition to the above-mentioned electrolyte components, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity and increasing the discharge capacity of the battery, the electrolyte may also include at least one additive selected from halogenated alkylene carbonate compounds (such as difluoroethylene carbonate, etc.), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol and aluminum chloride, etc. In this case, the content of the additive may be 0.1 wt% to 5 wt% relative to the total weight of the electrolyte.
[0072] As described above, since the lithium secondary battery including the positive electrode active material of the present invention stably exhibits excellent discharge capacity, excellent output characteristics and excellent capacity retention rate, it can be used in the fields of portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0073] Therefore, another aspect of the present invention provides a battery module including the lithium secondary battery as a unit cell, and a battery pack including the battery module.
[0074] The battery module or battery pack can be used as a power source for one or more medium- and large-sized devices selected from the group consisting of: power tools; electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); and power storage systems.
[0075] Example
[0076] The present invention will be described in more detail below with reference to embodiments, so that those skilled in the art can easily implement the present invention in a manner to describe the present invention in detail. However, the present invention can be presented in many different forms, and is therefore not limited to the embodiments described herein.
[0077] Example 1
[0078] Adding lithium source LiOH to the positive electrode active material precursor Ni 0.85 Co 0.05 Mn 0.10(OH)2, so that the Li / metal (Ni, Co and Mn) molar ratio is 1.15, then mixed, 1 wt% of B2O3 and 1 wt% of K2CO3 are added and mixed. For the primary heat treatment, the mixed powder is put into an alumina crucible. After that, it is fired at 850°C for 20 hours under an oxygen atmosphere to prepare a lithium composite transition metal oxide. Then, the lithium composite transition metal oxide is pulverized, rinsed and dried to obtain a powder, and the resulting powder is mixed with 0.1 wt% of H3BO3 and subjected to a secondary heat treatment at 300°C in an air atmosphere to obtain a positive electrode active material in the form of a single particle.
[0079] Example 2
[0080] A positive electrode active material was prepared in the same manner as in Example 1, except that the Li / metal (Ni, Co, and Mn) molar ratio was 1.11, and the temperature of the primary heat treatment was 830°C.
[0081] Example 3
[0082] A positive electrode active material was prepared in the same manner as in Example 1, except that the Li / metal (Ni, Co, and Mn) molar ratio was 1.18, and the temperature of the primary heat treatment was 870°C.
[0083] Example 4
[0084] A positive electrode active material was prepared in the same manner as in Example 1, except that the Li / metal (Ni, Co, and Mn) molar ratio was 1.18, and the temperature of the primary heat treatment was 890°C.
[0085] Comparative Example 1
[0086] A positive electrode active material was prepared in the same manner as in Example 1, except that the Li / metal (Ni, Co, and Mn) molar ratio was 1.05, and the temperature of the primary heat treatment was 950°C.
[0087] Comparative Example 2
[0088] A positive electrode active material was prepared in the same manner as in Example 1, except that the Li / metal (Ni, Co, and Mn) molar ratio was 1.02, and the temperature of the primary heat treatment was 780°C.
[0089] Comparative Example 3
[0090] A positive electrode active material was prepared in the same manner as in Example 1, except that the Li / metal (Ni, Co and Mn) molar ratio was 1.02, the primary heat treatment temperature was 780°C, and 1 wt% B2O3 and 1 wt% K2CO3 were not added.
[0091] [Experimental Example 1: Confirmation of the Surface Structure of the Positive Electrode Active Material]
[0092] The surface phase analysis of the positive electrode active materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was performed using transmission electron microscopy (TEM). Then, the maximum straight line length of the portion occupied by each phase was measured, and their ratio was calculated to measure the ratio of the Fd3M space group to the Fm3m space group in the 100nm region extending from the particle surface to the center (Fd3M / Fm3m). The results are shown in Table 1 below, and the TEM image of Example 2 is shown in Table 1 below. Figure 1 Shown in.
[0093] Table 1
[0094] Is it a single particle? Ratio in 100nm region (Fd3M / Fm3m) Example 1 O 0.2 Example 2 O 0.45 Example 3 O 0.6 Example 4 O 0.7 Comparative Example 1 O 0.05 Comparative Example 2 O 1.2 Comparative Example 3 X 1.2
[0095] Referring to Table 1, Examples 1 to 4 exhibited a phase ratio (Fd3M / Fm3m) satisfying a range of 0.2 to 0.7, whereas Comparative Examples 1 to 3 exhibited a phase ratio (Fd3M / Fm3m) outside the range. Figure 1 , the crystal structures of the Fd3M and Fm3m space groups on the particle surface could be determined, and it was confirmed that the phase ratio (Fd3M / Fm3m) was 0.45 when the maximum straight line length of each part was measured.
[0096] [Experimental Example 2: Charging / discharging efficiency]
[0097] The positive electrode active materials prepared in Examples 1 to 4 and Comparative Example 1, carbon black as a conductive material, and PVdF as a binder were mixed in an N-methylpyrrolidone solvent at a weight ratio of 96:2:2 to prepare a positive electrode mixture (viscosity: 5,000 mPa·s), and the positive electrode mixture was applied to one surface of an aluminum current collector, dried at 130° C. and roll-pressed to prepare a positive electrode.
[0098] Lithium metal was used as the negative electrode.
[0099] A porous polyethylene separator is placed between the prepared positive electrode and negative electrode to prepare an electrode assembly. Then, the electrode assembly is placed in a housing, and an electrolyte solution is injected into the housing to prepare a lithium secondary battery. In this case, the electrolyte solution is prepared by dissolving 1.0M lithium hexafluorophosphate (LiPF6) in an organic solvent containing ethylene carbonate, ethyl methyl carbonate and diethyl carbonate (the volume mixing ratio of EC / EMC / DEC is 3 / 4 / 3).
[0100] Each prepared lithium secondary battery (half cell) was subjected to charge / discharge test in the following manner: charged at 0.2C to 4.25V (final current: 1 / 20C) at 25°C in CC / CV mode, and discharged at a constant current of 0.2C to 3.0V, and its charge / discharge capacity and efficiency are shown in Table 2 below.
[0101] Table 2
[0102]
[0103] Referring to Table 2, it can be seen that, compared with the lithium secondary battery including the cathode active material of Comparative Example 1, the lithium secondary batteries including the cathode active materials of Examples 1 to 4 exhibited increased capacity and improved efficiency.
[0104] [Experimental Example 3: Resistance Characteristics]
[0105] As in Experimental Example 2, lithium secondary batteries (half cells) prepared using each positive electrode active material prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were discharged at 1.0C to 10% SOC at 25°C, and the direct current (DC) resistance was measured. When the discharge was performed at 1.0C for 10 seconds at the corresponding SOC, the resistance was calculated based on the voltage drop and the applied current value. The resulting resistance values are shown in Table 3 below.
[0106] Table 3
[0107]
[0108] Referring to Table 3, it can be seen that, compared with the lithium secondary batteries including the positive electrode active materials of Comparative Examples 1 and 2, the lithium secondary batteries including the positive electrode active materials of Examples 1 to 4 exhibit significantly improved resistance characteristics.
[0109] [Experimental Example 4: High Temperature Life Characteristics]
[0110] A lithium secondary battery (full battery) was manufactured using each positive electrode active material prepared in Examples 1 to 4 and Comparative Examples 1 to 3. The lithium secondary battery (full battery) was manufactured in the same manner as in Experimental Example 2, except that graphite as a negative electrode active material, carbon black as a conductive material, and PVdF as a binder were mixed in an N-methylpyrrolidone solvent at a weight ratio of 96:2:2 to prepare a negative electrode mixture, and the negative electrode mixture was applied to one surface of a copper current collector, dried at 130°C and rolled to manufacture a negative electrode.
[0111] The capacity retention rate and discharge resistance of each manufactured lithium secondary battery (full battery) were calculated by evaluating 100 cycles at 45°C with 0.7C / 0.5C. When a 4.25V fully charged battery was discharged at 0.5C for 60 seconds, the resistance was calculated based on the voltage drop and the applied current value. The capacity retention rate and resistance growth rate at the 100th cycle are shown in Table 4 below.
[0112] Capacity retention rate = (discharge capacity at the 100th cycle / discharge capacity at the 1st cycle) × 100
[0113] Resistance growth rate = (discharge resistance at the 100th cycle / discharge resistance at the 1st cycle) × 100
[0114] Table 4
[0115]
[0116] Referring to Table 4, compared with when the positive electrode active materials of Comparative Examples 1 to 3 were used, when the positive electrode active materials of Examples 1 to 4 were used, the capacity retention rate and the resistance growth rate after 100 cycles were significantly improved.
[0117] [Experimental Example 5: Continuous Discharge Characteristics]
[0118] As in Experimental Example 2, lithium secondary batteries (half cells) were manufactured using each of the positive electrode active materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3. The manufactured lithium secondary batteries (half cells) were charged to 4.7 V and then kept in CV mode for 120 hours. In this case, the generated current value was integrated and divided by time to calculate the average current value, and the results are shown in Table 5 below.
[0119] Table 5
[0120]
[0121] Referring to Table 5, when the positive electrode active materials of Examples 1 to 4 were used, the average current value generated for 120 hours was significantly lower than when the positive electrode active materials of Comparative Examples 1 to 3 were used.
Claims
1. A positive electrode active material for a secondary battery, which is a lithium composite transition metal oxide and is in the form of single particles. The lithium composite transition metal oxide contains nickel, cobalt, and manganese, and its nickel content accounts for 60 mol% or more of the metals other than lithium. in, Taking the 100 nm region extending from the particle surface of the lithium composite transition metal oxide toward the center as the particle surface portion of the lithium composite transition metal oxide, the particle surface portion has a crystal structure of the Fd3M space group and the Fm3m space group, and wherein, in the cross-sectional image of the particle surface portion of the lithium composite transition metal oxide particles obtained by using transmission electron microscopy (TEM), the ratio Fd3M / Fm3m measured is 0.2 to 0.
7. The ratio is the ratio of the maximum linear length of the portion occupied by the crystal structure of the Fd3M space group to the crystal structure of the Fm3m space group. The single particle form is a single particle form formed by one primary particle, or a secondary particle form formed by agglomerating up to 10 primary particles.
2. The positive electrode active material according to claim 1, wherein The ratio Fd3M / Fm3m is 0.3 to 0.
6.
3. The positive electrode active material according to claim 1, which has an average particle size D of 2 to 7 μm 50 in the form of single particles.
4. The positive electrode active material according to claim 1, wherein The cation mixing ratio of nickel cations in the lithium layer of the lithium composite transition metal oxide structure is 1.5% or less.
5. The positive electrode active material according to claim 4, wherein The cation mixing ratio of nickel cations in the lithium layer of the lithium composite transition metal oxide structure is 1.0% or less.
6. The positive electrode active material according to claim 1, wherein The molar ratio Li / M of lithium to the metal M other than lithium in the lithium composite transition metal oxide is 1.1 to 1.
2.
7. The positive electrode active material according to claim 1, wherein The lithium composite transition metal oxide is represented by the following Chemical Formula 1: [Chemical Formula 1] Li a Ni 1-b-c-d Co b Mr c Q d O 2+δ In Chemical Formula 1, Q is one or more elements selected from the group consisting of Al, Mg, V, Ti, and Zr, and satisfies 1.0 ≤ a ≤ 1.2, 0 < b ≤ 0.4, 0 < c ≤ 0.3, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.4, and -0.1 ≤ δ ≤ 1.
0.
8. A positive electrode for a secondary battery, which contains the positive electrode active material according to any one of claims 1 to 7.
9. A lithium secondary battery, which contains the positive electrode according to claim 8.
